2018
DOI: 10.1002/jcp.26327
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA XIST regulates myocardial infarction by targeting miR‐130a‐3p

Abstract: The study was employed to probe long non-coding RNA X-inactive specific transcript RNA (lncRNA XIST) expression profile and its influence on cell cycle, proliferation and apoptosis in myocardial cells. We also aimed to explore the possible meditating relationship between XIST, PDE4D and miR-130a-3p. Gene differential analysis was carried out using Human LncRNA Microarray V3.0. Quantitative real-time PCR (qRT-PCR) was used to test mRNA expressions of XIST, miR-130a-3p and PDE4D in normal cells and post-myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…Increasing evidences showed that lncRNA Xist was reported as an oncogene in various tumors [39,40]. Moreover, recent studies indicated the involvement of lncRNA Xist in myocardial infarction [41]. In this study, lncRNA Xist serve as a sponge of miR-19a-3p in BMSCs, and lncRNA Xist regulated Hoxa5 expression and BMSCs osteogenic differentiation via targeting miR-19a-3p directly.…”
Section: Discussionmentioning
confidence: 58%
“…Increasing evidences showed that lncRNA Xist was reported as an oncogene in various tumors [39,40]. Moreover, recent studies indicated the involvement of lncRNA Xist in myocardial infarction [41]. In this study, lncRNA Xist serve as a sponge of miR-19a-3p in BMSCs, and lncRNA Xist regulated Hoxa5 expression and BMSCs osteogenic differentiation via targeting miR-19a-3p directly.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, Guo et al showed that LINC00528 was one of the most upregulated lncRNA in MI tissues compared to normal tissues [15]. Zhou et al revealed that LINC00528 was one of the most upregulated lncRNA in CHD tissues compared with normal tissues [14]. However, the roles and underlying mechanisms of LINC00528 in MI progression remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been highlighted as key factors in the progression of AMI. Recently, studies showed that LINC00528 was one of the most upregulated lncRNA in coronary heart disease [14,15]. However, the roles and underlying mechanisms of LINC00528 in MI remain unclear.…”
Section: Linc00528 Expression In MImentioning
confidence: 99%
“…Zhou et al demonstrated XIST promoted myocardial infraction by targeting miR-130a-3p [7]. knockdown of lncRNA MIAT was identified to inhibit angiotensin II (Ang-II)-induced cardiac hypertrophy by targeting miR-93/TLR4 axis [8].…”
Section: Introductionmentioning
confidence: 99%